Production, purification and characterization of cholesterol oxidase from a newly isolated streptomyces sp. - Niwas, Ram; Singh, Vineeta; Singh, Rajbir; Tripathi, Divya; Tripathi, C. K. M. (World Journal of Microbiology & Biotechnology, 2013)
Cholesterol oxidase production (COD) by a new isolate characterized as Streptomyces sp. was studied in different production media and fermentation conditions. Individual supplementation of 1 % maltose, lactose, sucrose, peptone, soybean meal and yeast extract enhanced COD production by 80-110 % in comparison to the basal production medium (2.4 U/ml). Supplementation of 0.05 % cholesterol (inducer) enhanced COD production by 150 %. COD was purified 14.3-fold and its molecular weight was found to be 62 kDa. V-max (21.93 mu M/min mg) and substrate affinity K-m (101.3 mu M) suggested high affinity of the COD for cholesterol. In presence of Ba2+ and Hg2+ the enzyme activity was inhibited while Cu2+ enhanced the activity nearly threefold. Relative activity of the enzyme was found maximum in triton X-100 whereas sodium dodecyl sulfate inactivated the enzyme. The enzyme activity was also inhibited by the thiol-reducing reagents like Dithiothreitol and beta-mercaptoethanol. The COD showed moderate stability towards all organic solvents except acetone, benzene and chloroform. The activity increased in presence of isopropanol and ethanol. The enzyme was most active at pH 7 and 37 A degrees C temperature. This organism is not reported to produce COD.
Keywords: Affinity chromatography; Cholesterol oxidase; HPLC; SDS PAGE; Streptomyces sp.